Experiences of primary caregivers caring for children living with human immunodeficiency virus attending the wellness clinic at Jubilee Hospital Hammanskraal - Bejane, Stella Mmatsatsi (University of Limpopo (Medunsa Campus), 2012)
ABSTRACT Background and problem statement The increase in AIDS related deaths of parents leave many children orphaned and some of these children live with HIV. These children are cared for by primary caregivers who are mostly elderly women. The primary caregivers experiences challenges when caring for the children living with HIV. These challenges may be physical, spiritual, psychological and social. The researcher conducted a study in order to explore the experiences of primary caregivers caring for children living with HIV. Aim and objectives The aim of the study was to promote the mental health of primary caregivers who provide care for children living with HIV attending the Wellness Clinic at the Jubilee Hospital in Hammanskraal. The objectives of this study were to: i) describe the biographical data of primary caregivers who provide care for children living with HIV; ii) explore and describe the experiences of primary caregivers who provide care for children living - with HIV; and iii) make recommendations which are based on the findings of this study in order to assist the nursing personnel at the Wellness Clinic in the promotion of the mental health of primary caregivers based on the findings of this study. Research Design and method A qualitative, exploratory, descriptive and contextual design was utilised to enable the primary caregivers to share with the researchers their experiences of caring for children living with HIV. The setting was the Wellness Clinic at the Jubilee hospital, Hammanskraal. Ethical principles were adhered to in order to protect the rights of the primary caregivers. Throughout the process, the methods to ensyre trustworthiness of the study were foll9wed. A purposive sample of eight primary caregivers was chosen for the unstructured interviews. Data were analysed by the researcher and an independent coder using the Tescn method. Research Findings Consensus was reached after consultation with an independent coder,- about the following categories i) primary caregivers' experiences in caring for a child living with HIV related to the self of the caregiver; ii) primary caregivers' experiences related to the decision to disclose the child's HIV status to various role-players were influenced by stigmatisation and discrimination related to HIV and AIDS; iii) primary caregivers' challenges when caring for a child living with HIV; and iv) the mobilisation of resources by primary caregivers to assist them in caring for a child living with HIV. Findings were contexualised by implementing a literature control and recommendations were made to promote their mental health. Conclusions Primary caregivers who cared for children living with HIV in this study were mostly elderly women who were related to the children. They took over the care of the children living with HIV after the children's parents had died. Although they were faced with many challenges, their concern for the children's wellbeing made them to give the children loving care. They found strength and support from prayer, faith and hope in God. The primary caregivers also appreciated the support they received from the health care workers at the Well"ness Clinic. Key words: caring, mental health, HIV, children, primary caregiver
Thesis (M Cur)-- University of Limpopo, 2012.
Keywords: Immunodeficiency virus; Caregivers